Evaluative research on teaching innovation with simulators in the area of Technology in Compulsory Secondary Education. - Micó-Amigo, Ester; Bernal Bravo, César (IJERI: International Journal of Educational Research and Innovation, 2020)
The meaning of knowledge through simulation implies knowing how to interpret everyday processes and situations. The knowing of mechanisms and technological operators involved, being competences that are worked with special attention in the Technology classroom and help to consolidate knowledge, awaken the interest of students and motivate them towards research in the field of science and technology, as well as their capacity for analysis and reasoning. The research methodology is an action research, common to evaluative studies of educational innovation in training processes and improvement of professional practice. The selection of this teaching experience is due, on the one hand, to its innovation proposal integrating the methodological strategy of "Problem-Based Learning (ABP) being the backbone of the Technology area. On the other hand, the use of simulators, playing a fundamental role in the implementation of those processes embodied in projects that solve simple day-to-day problems. The emerging critical explanatory categories - selected for this work - have been; interest in solving technical problems, in robotics sessions, and programming simple mechanisms. As a result, the design of educational experiences based on the simulation of mechanisms or processes through digital media awakens the interests of the students as well as other sensations and emotions linked to the great diversity of content developed in the computer room, highlight the themes current technological booming as programming, simulation of structures, mechanical movements or electrical and automatic circuits.